Entre pétalas e espinhos: qualidade e violência na conjugalidade - Razera, Josiane (Universidade do Vale do Rio dos Sinos, 2014)
Violent conjugal relationships may cause serious health problems to those who are involved, and spouses find it difficult to recognize violence, tending to remain in such relationships. Thus, in Section I, the objective was to measure levels of quality and violence of conjugal relationships, as well as the relation between these dimensions with sociodemographic characteristics of the sample and the predictive power of the different types of violence in the conjugal quality. The participants were 186 heterosexual couples, officially married or in common-law marriage. Analyses showed that scores in psychological violence were over 85% of the sample, however, 66.5% of the couples assessed conjugal quality between average and very good, and 33.5% between poor and very severe problems. There was a positive correlation between the variables quality and violence, and psychological aggression was the dimension with more predictive power to conjugal problems. In Section II, the objective was to investigate how spouses assessed their intimate relationships with the presence of violence, and which aspects led them to remain in such relationships. Multiple case studies (Yin, 2005) analyzed four couples who experienced psychological, physical, or sexual violence. Different reasons were recognized as triggers for conflict, such as children education, betrayal, alcoholism, and financial issues. In some cases, remaining in such relationships is justified by practicality, and in others, love is what keeps them together. All cases showed that, although they speak about violent episodes, couples do not recognize violence or minimize the seriousness of the problem. For couples who want to remain together, it is important to work with conflict resolution strategies that are different from violence, promoting more health among them.
Keywords: Relacionamentos conjugais; Qualidade conjugal; Violência conjugal; Conjugal relationships; Conjugal quality; Conjugal violence; ACCNPQ::Ciências Humanas::Psicologia